Bypassing the Immunosuppression of Myeloid‐Derived Suppressor Cells by Reversing Tumor Hypoxia Using a Platelet‐Inspired Platform. (6th April 2020) - Zhang, Chao; Xia, Donglin; Liu, Jiahao; Huo, Da; Jiang, Xiqun; Hu, Yong
Abstract: Myeloid‐derived suppressor cells (MDSCs) are garnering increasing attention given their role in tumor development. Herein, a nano‐enabled strategy is demonstrated for the eradication of tumor‐infiltrated MDSCs by reversing hypoxia. Oxygen‐independent photodynamic bismuth tungstate nanoparticles (Bi2 WO6 NPs) are loaded into reactive oxygen species (ROS) responsive platelet membranes (PMs) to form a hybrid (PM‐BiW NPs). P‐Selectin on PMs endows PM‐BiW NPs with selectivity toward cancer cells. Once in the tumor, laser illumination stimulates the Bi2 WO6 NPs photothermally and photodynamically, which produces enormous quantities of hydroxyl radicals. These hydroxyl radicals help rupture the PM and mitigate hypoxia with the assistance of ionizing radiation. This effectively remodels the tumor microenvironment toward one disfavoring the recruitment of MDSCs and contributes to better prognosis. To better understand the mechanism, the expression levels of a set of markers are monitored. It is found that the downregulations of hypoxia‐inducible factor‐1α, ectonucleoside triphosphate diphosphohydrolase 2, and adenosine‐5‐phosphoricacid are behind the blocked infiltration of MDSCs. This platform strategy offers a promising approach to overcome the immunosuppression caused by MDSCs through a trimodal therapy integrating the power of photothermal and photodynamic therapy in addition to radiation therapy. Abstract : The generation of OH from platelet membranes‐coated bismuth tungstate nanoparticles in the phototherapy treatment effectively alleviates the anabatic tumor hypoxia in radiotherapy (RT) via a radical‐boosted RT sensitivity approach. Subsequently, the frequency of myeloid‐derived suppressor cells detected in tumor tissues dramatically declines, which strikingly promotes T cell recruitment and activation, and improves treatment outcome.